Clinical Characteristics and Survival of Korean Idiopathic Pulmonary Arterial Hypertension Patients Based on Vasoreactivity - Ahn, Jee Hwan; Kang, Byung Ju; Hong, Sun In; Lee, Jung Su; Lee, Jae Seung; Oh, Yeon-Mok; Lee, Sang-Do (Journal of Korean medical science, 2014)
We aimed to identify a vasoreactive subset of patients with idiopathic pulmonary arterial hypertension (IPAH) in Korea and to show their clinical characteristics and prognosis. Data on patients who were diagnosed with IPAH at Asan Medical Center between January 1994 and March 2013 were retrospectively collected. Acute vasodilator testing was performed with inhaled nitric oxide during diagnostic right heart catheterization. A positive acute response was defined as a reduction in mean pulmonary arterial pressure (PAP) ≥10 mmHg to an absolute level of mean PAP <40 mmHg without a decrease in cardiac output. Among a total of 60 IPAH patients included for analysis, 9 (15%) showed a positive acute response to acute vasodilator testing. Acute responders showed significantly lower peak velocity of a tricuspid regurgitation jet on echocardiography (4.1±0.3 m/s vs. 4.6±0.6 m/s; P=0.01) and significantly lower mean PAP hemodynamically (47±10 mmHg vs. 63±17 mmHg; P=0.003) than non-responders at baseline. The survival rate of acute responders was 88% at 1, 3, 5, and 10 yr, respectively, which was significantly higher than that of non-responders (85%, 71%, 55%, and 40%, respectively; P=0.029). In conclusion, Korean IPAH patients with vasoreactivity showed better baseline hemodynamic features and survival than those without vasoreactivity.